Smoking reduction and quality of life in chronic patients with schizophrenia in a Chinese population—A pilot study. Issue 2 (29th January 2016) - Deng, Huiqiong; Wang, Jia; Zhang, Xiangyang; Ma, Mengying; Domingo, Coreen; Sun, Hongqiang; Kosten, Thomas
Abstract : Background and Objectives: Tobacco use is a significant public health issue on a global scale. Prevalence of daily tobacco smoking for men in China is much higher than in the United States. Although prevailing literature suggests a negative relationship between smoking and quality of life, this pilot study sought to evaluate whether smoking reduction/cessation impacted on the perception of quality of life in an in‐patient population in China. Methods: Twenty Chinese patients meeting DSM‐IV criteria for schizophrenia were recruited from Beijing Hui‐Long‐Guan Hospital, an in‐patient facility in Beijing, China, for participation in this 4‐week study. Seventeen participants with schizophrenia completed the study and were included in the final analysis. Cigarette consumption was recorded daily and the World Health Organization Quality of Life‐BREF (WHOQOL‐BREF) was completed at baseline and at week 4. The relationships between smoking and perceived quality of life were evaluated using correlations between changes in WHOQOL‐BREF and changes in cigarettes consumed as measured from baseline to week 4. Results: We found an increase in perceived quality of life in the social relationships domain with increased cigarette consumption in contrast to a decrease in this domain with decreased consumption. However, decreased cigarette consumption was associated with an increase in the psychological domain compared to the social domain. Conclusions and Scientific Significance: These associations suggest a need for interventions to improve the social relationship perceptions with any successful reduction in cigarette consumption among Chinese schizophrenics in order to match their perceived psychological improvement. (Am J Addict 2016;25:86–90)